Association of patent ductus arteriosus size with clinical features and short-term outcomes in preterm infants less than 34 weeks - Shekharappa, Chandrakala Bada; Elizabeth, Edison Albert Balakrishnan; Balachander, Bharathi (Indian Journal of Child Health, 2020)
Background: Preterm patent ductus arteriosus (PDA) is a challenging situation faced by the neonatologists every day. The devastating consequences of a hemodynamically significant PDA (hsPDA) compared to the harms of medical therapy, make treatment decisions challenging. The diagnosis of an hsPDA is not uniform and multiple classifications are available to assess its severity. Aim: The present study was aimed to analyze whether the size of PDA, based on echocardiography, had any association with clinical features and neonatal outcomes. Materials and Methods: This retrospective study was done in a Level 3 newborn intensive care unit (NICU) from January 2016 to December 2017. Preterm (?34 weeks) infants with hsPDA formed the study group. Data were collected from the NICU database. hsPDA was classified based on the size into small, moderate, and large and analysis was done. Data for each infant until discharge were collected in pre-designed pro forma from medical records. Results: A total of 1064 preterm infants were admitted during the study period and 94 had hsPDA. The mean gestational ages were 31.8±4.2, 29.6±3.3, and 31.9±4.2 weeks for mild, moderate, and severe PDA, respectively. Among the clinical parameters, it was found that shock, metabolic acidosis (p<0.01), and thrombocytopenia were significantly associated with larger PDA size (p=0.02). Infants with a larger PDA size had a higher risk of bronchopulmonary dysplasia (BPD) and ventilation days (p=0.03). Logistic regression was done to analyze independent factors associated with shock, BPD, and PDA severity. Conclusion: Large PDA is associated with an increased risk of higher ventilation days and BPD.